2015
DOI: 10.3390/s151127969
|View full text |Cite
|
Sign up to set email alerts
|

Automated Identification of River Hydromorphological Features Using UAV High Resolution Aerial Imagery

Abstract: European legislation is driving the development of methods for river ecosystem protection in light of concerns over water quality and ecology. Key to their success is the accurate and rapid characterisation of physical features (i.e., hydromorphology) along the river. Image pattern recognition techniques have been successfully used for this purpose. The reliability of the methodology depends on both the quality of the aerial imagery and the pattern recognition technique used. Recent studies have proved the pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
96
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 30 publications
0
96
0
1
Order By: Relevance
“…Future work might consider the use of drone-mounted optical systems operating beyond the visible range of the spectrum, particularly in the near-infrared and shortwave infrared regions of spectrum where water bodies are spectrally distinct [25]. Efforts could also be made in the future for automatic detection of water bodies using drone imagery (such as Casado et al [48]); the calibration/training of such models, however, is relatively time-consuming and therefore manual interpretation and delineation of water bodies, as demonstrated to be successful in this study, represents a more operationally valid option for malaria managers.…”
Section: Resultsmentioning
confidence: 99%
“…Future work might consider the use of drone-mounted optical systems operating beyond the visible range of the spectrum, particularly in the near-infrared and shortwave infrared regions of spectrum where water bodies are spectrally distinct [25]. Efforts could also be made in the future for automatic detection of water bodies using drone imagery (such as Casado et al [48]); the calibration/training of such models, however, is relatively time-consuming and therefore manual interpretation and delineation of water bodies, as demonstrated to be successful in this study, represents a more operationally valid option for malaria managers.…”
Section: Resultsmentioning
confidence: 99%
“…UAS-technology is also especially favourable for monitoring purposes with short and/or user-defined repetition intervals. Our automated classification approach for water versus vegetation and at the growth-form level is highly applicable in lake and river management [53] and aquatic plant control, such as in evaluation of rehabilitation measures [54]. Valta-Hulkkonen et al [55] also found that a lake's degree of colonisation by helophytes and nymphaeids detected by remote sensing was positively correlated with the nutrient content in the water.…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning tools are almost ubiquitously applied to rapidly classify images, from fine [34] to broad scales [35]. These methods are also being used in fisheries, where researchers are combining sonar sensing methods and machine learning tools (e.g., [36]).…”
Section: Image Classificationmentioning
confidence: 99%